A research on academic self-perception and academic achievement of secondary school students - Şenay Bozdağ; Sümer Aktan (Literacy Trek)
The aim of the present study is to investigate the connection between academic self-perception and academic achievement of seventh-grade secondary school students in English courses. Additionally, the study aims to explore the relationship between various demographic factors and academic achievement in English. A predictive correlational research design and causal comparison methods were employed. The sample consisted of 906 volunteer seventh-grade students from public secondary schools in Altıeylül and Karesi, Balıkesir Province. The 19-item, 4-point Likert-type "Academic Self-Perception Scale," developed by Liu, Wang, and Parkins (2005), was adapted into Turkish by the researchers for this study. An original measurement tool was also utilized to assess achievement in English language courses. Demographic variables were analyzed using t-tests, ANOVA, and structural equation modeling. Pearson correlation analysis, simple linear regression analysis, and stepwise multiple hierarchical regression analysis were applied to determine the relationship between academic self-perception and achievement in English language courses. Results indicated a significant, positive, and moderate relationship between academic self-perception and achievement in English language courses. Regression analysis revealed that academic self-perception significantly predicts achievement in English language courses. Furthermore, achievement in English language courses varied significantly based on the variables of having a study room and the father's level of education.